Improving Basic Locomotor Movement Skills in Elementary School Students Through an Active Learning Approach Based on Traditional Games - Fadlan, Muhammad Noer; Dwi, Dara Fitrah; Anshor, Arrini Shabrina; Landong, Ahmad (Institut Agama Islam Negeri Palopo, 2023)
This research aims to improve basic locomotor movement skills in grade 5 elementary school students through active learning interventions based on traditional games. In this research, researchers used a quasi-experimental research design with stratified random sampling. Two groups of students were selected, where one group was given active learning intervention, while the other group was a control group that received conventional learning. The research instruments used included basic movement skills tests, student response questionnaires, participant observation, and field notes. The collected data was analyzed using descriptive statistical methods and the T test to compare the differences between the two groups before and after the learning intervention. The statistical calculation method used was the T test, which was used to compare the differences between the experimental group and the control group in terms of improvement in basic locomotor movement skills after the intervention. By using the T test, researchers can evaluate whether there are significant differences between the two groups and whether traditional game-based active learning interventions are effective in improving the basic movement skills of grade 5 elementary school students. The research results show that traditional game-based active learning interventions have a significant positive impact in improving basic locomotor movement skills in grade 5 students. This shows the important potential of interactive and fun learning methods in improving the quality of learning and the development of students' motor skills. In conclusion, active learning interventions based on traditional games can be effective in improving basic locomotor movement skills in grade 5 elementary school students. This research provides important implications for the development of a more inclusive and student-centered curriculum at the elementary school level.